Analisis Penataan Sel Untuk Layanan Sistem WCDMA Di Area Jalan Tengah I Kerobokan - Winaya, Alit; Sukadarmika, Gede; Linawati, Linawati (Majalah Ilmiah Teknologi Elektro; Vol 16 No 2 (2017): (May - Agustus) Majalah Ilmiah Teknologi Elektro, 2017)
In WCDMA system, signal service coverage determines quality service of telecommunication network . To give maximum network service at Jl. Tengah I Kerobokan area, thus requiring the study of the arrangement of the cell coverage on BTS Protpeliatan Sector ? and BTS AnyarKaja Sektor ?. The method used is calculation the distance of base station with proper propagation model which suits the condition of both base stations, also antenna azimuth and tilting were given, and simuation using Atoll software to see the predicted coverage area of BTS. As the result, suitable propagation for BTS Protpeliatan Sector ? is Okumurra Hatta model and BTS AnyarKaja Sektor ? is Cost 231 Hatta model, maximum coverage signal service of BTS Protpeliatan Sector ? is 1,17 km and for BTS AnyarKaja Sektor ? is 1,11 km. Requirement of antenna tilt change from 0º to 0,95º for BTS Protpeliatan Sektor ? and for pada BTS AnyarKaja Sektor ?, antenna tilt change from 0º to 1º and change of 30º antenna sector direction from 180º to 210º. From simulation using Atoll software with above parameters, acknowledge that area of Jl. Tengah I Kerobokan already get maximum service with received signal level pass the KPI (Key Performance Indicator) standard.
Keywords: Cakupan layanan, BTS, model propagasi, tilt, sektorisasi, antena, atoll, WCDMA